Proximity of restored hedgerows interacts with local floral diversity and species' traits to shape long‐term pollinator metacommunity dynamics - Lauren C. Ponisio; Perry de Valpine; Leithen K. M’Gonigle; Claire Kremen (Ecology Letters, 2019)
Disconnected habitat fragments are poor at supporting population and community persistence; restoration ecologists, therefore, advocate for the establishment of habitat networks across landscapes. Few empirical studies, however, have considered how networks of restored habitat patches affect metacommunity dynamics. Here, using a 10‐year study on restored hedgerows and unrestored field margins within an intensive agricultural landscape, we integrate occupancy modelling with network theory to examine the interaction between local and landscape characteristics, habitat selection and dispersal in shaping pollinator metacommunity dynamics. We show that surrounding hedgerows and remnant habitat patches interact with the local floral diversity, bee diet breadth and bee body size to influence site occupancy, via colonisation and persistence dynamics. Florally diverse sites and generalist, small‐bodied species are most important for maintaining metacommunity connectivity. By providing the first in‐depth assessment of how a network of restored habitat influences long‐term population dynamics, we confirm the conservation benefit of hedgerows for pollinator populations and demonstrate the importance of restoring and maintaining habitat networks within an inhospitable matrix.